Ultimate pit limit determination for fully mobile in-pit crushing and conveying systems. (10th January 2020) - Hay, Edward; Nehring, Micah; Knights, Peter; Kizil, Mehmet S.
Fully-mobile in-pit crushing and conveying systems have different pit shape requirements to traditional truck haulage systems due to linear bench and flat floor constraints imposed by conveyor systems. As the shape of a pit is largely based on the ultimate pit limit, it is desirable to have the additional shape requirements of fully mobile in-pit crushing and conveying systems included in the ultimate pit limit determination process. This paper discusses and highlights why there are different requirements for these systems, and what they are. A method of including these extra requirements during ultimate pit limit determination is presented. A case study has been included to show the method working, with scheduling of the pits to further highlight the viability of fully mobile in-pit crushing and conveying. This case study shows that through the reduced mining costs, a fully mobile in-pit crushing and conveying pit can return a higher net present value than the traditional truck and shovel pit for the same deposit. The development of this method provides the opportunity for the metalliferous industry to accurately determine ultimate pit limits for mines considering the use of fully mobile in-pit crushing and conveying systems.